Phylogenetic reconstruction of four poultry populations using stepwise mutation model - VIJH, R K; MISHRA, BINA; PANDEY, A K; CHOUDHARY, PREETI; TANTIA, M S (The Indian Journal of Animal Sciences, 2014)
The data on 26 microsatellite loci was generated for 4 poultry populations viz; Aseel, Miri, Nicobari and Kashmir Favorolla. The data were analyzed for 4 genetic distances-ASD, DSW, (Âµ)2 and similarity index using Stepwise Mutation model. The phylogenetic tree and topology was constructed using UPGMA algorithm, The Aseel and Nicobari breeds of poultry were more closely related to one another than with Miri and Kashmir Favorolla. The phylogenetic tree and topology using genetic distance and squared genetic distances have been presented.